SISTEM INFORMASI PEMESANAN BERBASIS WEB PADA PT. VERMINDO UTAMA SEMARANG - Siswanto Siswanto (Elkom : Jurnal Elektronika dan Komputer, 2018)
PT. Vermindo Utama Semarang having its address at Jl. Pawiyatan Luhur Number 25 Semarang is a company engaged in the distribution and production of goods, especially health products. PT. Vermindo Utama Semarang has dozens of Salesmen and a leader. PT. Vermindo Utama Semarang carries out the process of buying and selling wholesale with various customers, the majority of whom are Pharmacies and supermarkets. In running its business, PT. Vermindo Utama Semarang still sells conventionally by using salesmen. And the marketing area still covers Central Java and East Java. Based on the problems above, the writer wants to propose a web-based booking system design to be considered in helping in the promotion of goods from PT. Vermindo Utama Semarang. Application Order System PT. Vermindo Utama Semarang by using PHP and MySql database. Making this application is expected to be one of the efforts that can be done to overcome the problems that often occur so as to increase the effectiveness of work which will certainly affect the quality of service to customers.